(untitled) (International Journal of Engineering and Computer Science, 2015)
As credit card is becoming more efficient for online financial transaction, at the same time fraud associated with it is also increasing. This method is to increase the security level of the society against the fraudsters. This paper is totally concerned with the feature of fingerprint authentication which makes the transaction more secure as compared to the traditional Credit/Debit card payment. Here we are going to implement fingerprint biometric authentication for identifying and verifying person. The fingerprint biometric authentication is used to authenticate the original user so that the unauthorized person should not be able to perform the transaction. If any suspicious transaction will occurred then proposed system blocked the current transaction and will notify the valid user on respective available information.